BIOGENIC MANGANESE OXIDES: PROPERTIES AND MECHANISMS OF FORMATION - Tebo B.M.; Clement B.G.; Dick G.J.; Murray K.J.; Parker D.; Verity R.; Bargar J.R.; Webb S.M. (My University, 2004)
Manganese(IV) oxides produced through microbial activity, i.e., bio-genic Mn oxides or Mn biooxides, are believed to be the most abundant and highly reactive Mn oxide phases in the environment. They mediate redox reactions with or-ganic and inorganic compounds and sequester a variety of metals. The major pathway for bacterial Mn(II) oxidation is enzymatic, and although bacteria that oxidize Mn(II) are phylogenetically diverse, they require a multicopper oxidase-like enzyme to oxidize Mn(II). The oxidation of Mn(II) to Mn(IV) occurs via a soluble or enzyme-complexed Mn(III) intermediate. The primary Mn(IV) biooxide formed is a phyllomanganate most similar to δ-MnO 2 or acid birnessite. Metal sequestration by the Mn biooxides occurs predominantly at vacant layer octahedral sites.
Keywords: bacterial Mn(II) oxidation; δ-MnO 2; birnessite; Mn bacteria; multicopper oxidase; X-ray absorption spectroscopy; Mn minerals